Multidimensional Trust in Halal Logo of Food Products : A Study in Local Cultural Context - Kusumastuti, Dani; Raharja, Mahardhika Cipta; Maamor, Selamah; Yulian, Tri Nurindahyanti (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Trust is a multidimensional concept that varies across cultures and societies. Understanding consumers' trust is essential to increase awareness of the halal logo. This study aims to examine the trust dimensions of the halal logo in the Penginyongan cultural region. Confirmatory factor analysis was employed to analyze data from a sample of 139 Muslims residing in the Penginyongan cultural area, which encompasses the regencies of Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen. The results show that spiritual, cognitive, and affective factors significantly influence trust in the halal logo on food and beverage products. Affective aspects have demonstrated the highest loading factor value, suggesting that affective approach must be prioritized in building trust in halal logo. This can be achieved by creating emotional branding and excellent service as the key to long-term consumer commitment to the halal logo. This study has broadened the understanding of trust in the halal logo in a particular culture and expanded the concept of trust by including the spiritual dimension as an important factor in enhancing trust.